Study on the Influence of Siloxane-Modified Polyether Amine Curing Agents on the Performance of Epoxy Linking Paint - PAN Xuelong, LU Ading, SUN Baoku, LIU Lin, ZHANG Xiru, ZHANG Haichun (Cailiao Baohu)
In order to address the poor compatibility between low surface energy antifouling coatings and conventional anticorrosive primers， a siloxane-modified polyether amine curing agent was prepared using the physical properties and active group characteristics of low surface energy antifouling coatings.Based on a conventional epoxy linking paint formulation， the influence of the siloxane-modified polyether amine curing agent on the micro-morphology， Shore A hardness， static water contact angle， and adhesion strength of the connecting coating was investigated to determine the amount of siloxane-modified polyether amine curing agent added to the specialized linking paint.After combining the specialized linking paint with the low surface energy antifouling coating， the system’s FTIR spectrum was tested， and performance tests for toluene/ammonia solution immersion and shallow seawater immersion were conducted to explore the interfacial reaction mechanisms and practical marine application performance of the specialized linking paint.Results showed that the amine hydrogen equivalent of the siloxane-modified polyether amine curing agent was between 200 and 300， and its rotational viscosity was between 180 and 250 mPa·s (at 25 ℃).The siloxane-modified polyether amine curing agent significantly improved the self-leveling properties of the specialized linking paint， reduced the Shore A hardness，increased the static water contact angle， and enhanced the compatibility between the different paint films.When the mass fraction of the siloxane-modified polyether amine curing agent was 6%， optimal adhesion with the antifouling topcoat was achieved， with adhesion strength reaching approximately 2.1 MPa， and stable and strong chemical bonding between the layers.The results of shallow seawater immersion tests were significantly superior to those of conventional epoxy linking paints.These findings effectively addressed the compatibility issues between low surface energy antifouling coatings and primers， extending the overall service life of the anticorrosive and antifouling coating system.